The Contribution of Fiscal Decentralization and Natural Resources on Economic Growth in Indonesia: Does Corruption Hamper? - Hannani, A Munif; Ananda, Candra Fajri (Universitas Syiah Kuala, 2024)
Objective This study aims to explain the effect of fiscal decentralization and natural resources on economic growth in Indonesia; and the moderating role of corruption in both fiscal decentralization-economic growth and natural resources-economic growth nexuses.Methodology This study uses quantitative approach by utilizing a moderated panel data regression analysis with cross-sectional observations of 34 provinces in Indonesia from 2011 to 2021.Results Fiscal decentralization has no significant effect on economic growth, while natural resources positively affect economic growth. Furthermore, we found no moderating effect of corruption in the fiscal decentralization-economic growth nexus, but the weakening effect of corruption is evident in the natural resources-economic growth nexus.Research limitation/implications To further encourage economic growth in the regional level, it is vital to impose budget composition requirements on regional governments in the framework of fiscal decentralization, particularly related to employee and capital expenditure; and to maintain the decentralization of natural resources management on the regional level, while continuing efforts on eradicating corruption.Novelty/OriginalityFew researchers consider the role of corruption as a moderator in the relationship between fiscal decentralization and natural resources on economic growth. This study fills this gap by incorporating a moderating role of corruption that may weaken the ability of fiscal decentralization and natural resources to promote economic growth with the evidence from Indonesias provinces.